Adaptive reuse of commercial and public buildings in Wroclaw Old Town in Poland. The occupant’s safety and comfort versus preservation of authenticity of monumental buildings - Kirschke, Krystyna; Kirschke, Paweł; Komarzyńska-Świeściak, Elżbieta (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
There are more than a hundred historic public buildings in the centre of Wrocław, adapted to fulfill modern commercial function. Against the background of today’s cosmopolitan shopping centers and office buildings, these buildings are distinguished by stylish architecture, maintained in eclectic, Art Nouveau or modernist forms. In the process of renewal of such monumental buildings, there is a need to reconcile the requirement for maximum protection of the historic material with safety and comfort of use. The multi-disciplinary construction design constituting the basis for the adaptive reuse of the heritage building must be preceded by conservation research and concept designs simulating possible program options. This allows linking the assessment of the value of the architecture with a choice of the matching function corresponding to the location and historic structure of the building. The further multi-disciplinary design process and implementation of such a project should be based on the Research by Design scheme. This allows for control of the implementation of the project and to rationalize the necessary upgrade of the facility with the application of such space and technical solutions that limit the destruction of its historic substance. The paper presents conclusions from several adaptive reuse projects carried out in such a way, in which it was possible to create high-class department stores, banks, hotels or prestigious offices inside the heritage buildings. The essence of these developments was to preserve the authenticity of the monumental building, while providing the necessary infrastructure, plant rooms and equipment guaranteeing safety and comfort of use.